2010
DOI: 10.1007/s12043-010-0216-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser pulse heating of nuclear fuels for simulation of reactor power transients

Abstract: It is important to study the behaviour of nuclear fuels under transient heating conditions from the point of view of nuclear safety. To simulate the transient heating conditions occurring in the known reactor accidents like loss of coolant accident (LOCA) and reactivity initiated accident (RIA), a laser pulse heating system is under development at BARC, Mumbai. As a prelude to work on irradiated nuclear fuel specimens, pilot studies on unirradiated UO2 fuel specimens were carried out. A laser pulse was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Also, there is a small kink around 28° that appears due to the probable formation of U 4 O 9 on heating of U 3 O 8 at elevated temperatures. 29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is a small kink around 28° that appears due to the probable formation of U 4 O 9 on heating of U 3 O 8 at elevated temperatures. 29…”
Section: Resultsmentioning
confidence: 99%
“…Also, there is a small kink around 281 that appears due to the probable formation of U 4 O 9 on heating of U 3 O 8 at elevated temperatures. 29 Previously reported work by Kelly et al 18 based on synchrotron X-ray measurements suggested that the Eu 3+ occupies the Li + site of LTB due to favorable size matching and higher oxygen coordination. The charge compensation will be taken care of by negatively charged cation vacancies, viz.…”
Section: Phase Vibrational Bands and Structural Analysesmentioning
confidence: 97%
“…Laser heating was used in this study to vaporize the samples in air and to generate aerosols that are typical for radioactive release. So far laser heating for simulating accidental scenarios was applied only in a few studies, in relation to reactor power transients [19,20]. Viswanadham et al [19] studied the effect of laser impulses on UO 2 pellets, while Zanotelli et al [20] (similar to our application) applied this technique for the production of aerosols and their characterisation.…”
Section: Instrumentation and Experimental Proceduresmentioning
confidence: 99%
“…So far laser heating for simulating accidental scenarios was applied only in a few studies, in relation to reactor power transients [19,20]. Viswanadham et al [19] studied the effect of laser impulses on UO 2 pellets, while Zanotelli et al [20] (similar to our application) applied this technique for the production of aerosols and their characterisation. The laser heating technique was chosen in the present experiments for various reasons: limiting interactions between the holder, the heating elements and the sample; avoiding radioactive contamination of the heating components; reaching extreme temperature transients; but especially to have a controlled and reproducible temperature of the sample.…”
Section: Instrumentation and Experimental Proceduresmentioning
confidence: 99%